Leveraging TPB to enhance credit card usage in Vietnam: Implications for financial literacy and banking innovation - Duong, Vinh Suong; Nguyen, Thi Thuy Huong; Phan, Anh; Nguyen, Thi Thuy Ngan; Dinh , Thi Linh (Edelweiss Applied Science and Technology, 2025)
This study examines the factors influencing individual customers’ decisions to use credit cards at Vietnamese commercial banks, applying an extended Theory of Planned Behavior framework. Based on data from 332 respondents, the research empirically validates six key determinants: Attitude, Subjective Norms, Perceived Behavioral Control, Card Usage Costs, Card Usage Convenience, and Bank Responsiveness. All factors exhibit a positive and statistically significant effect on credit card adoption, with Perceived Behavioral Control emerging as the strongest predictor. The convenience of card usage and responsiveness of banking services also play substantial roles, highlighting the importance of operational efficiency and user experience. The findings affirm the robustness of the original theory while emphasizing the value of incorporating context-specific elements, particularly in emerging markets. Methodologically, the study adopts a quantitative approach using structured questionnaires and regression analysis. Practical implications are proposed for both commercial banks and policymakers, including educational programs, digital banking enhancements, transparent pricing policies, and nationwide financial literacy initiatives. These measures aim to foster greater consumer confidence and encourage wider adoption of cashless payment solutions. The research offers theoretical contributions and lays the groundwork for future studies on consumer finance behavior in developing economies.